Change in vision-related quality of life and influencing factors in Asians receiving treatment for neovascular age-related macular degeneration. Issue 3 (28th June 2017) - Fenwick, Eva K; Cheung, Gemmy Chui Ming; Gan, Alfred TL; Tan, Gavin; Lee, Shu Yen; Wong, Doric; Yeo, Ian; Mathur, Ranjana; Wong, Tien Y; Lamoureux, Ecosse L
Abstract : Aim: To assess the change in vision-related quality of life (VRQoL) after treatment for neovascular age-related macular degeneration (nAMD) and factors influencing this change in an Asian population. Methods: In this longitudinal study, 116 patients (mean age±SD=66.5±9.9 years; 59.5% male) who underwent treatment for nAMD were recruited from a tertiary eye centre in Singapore. Best-corrected visual acuity (BCVA) and the Impact of Vision Impairment (IVI) questionnaire were evaluated at baseline and month 12. We defined three categories of BCVA change in the treated eye: BCVA gain ≥2 lines; no change in BCVA; BCVA loss ≥2 lines. The main outcome measures were the Rasch-derived IVI Reading, Mobility, and Emotional Scores. Multivariable linear regression analyses assessed the influence of sociodemographic, clinical and treatment-related factors on change in VRQoL. Results: Following treatment, mean treated-eye BCVA improved by almost 2 lines (−0.22±0.40 logMAR, p<0.001) and 43% (n=50) patients reported a gain in BCVA of ≥2 lines. Mean±SD scores for Reading, Mobility and Emotional demonstrated positive changes of 0.43±1.73, 0.45±1.54 and 0.66±1.6, respectively (p<0.001 for all). In multivariable models, a ≥2 line improvement in BCVA was independently associated with a 47% (β=0.20; CI 0.01 to 0.39) increase in Reading Scores, but was not independently associated with Mobility or Emotional Scores. Conclusion: Nearly half of patients undergoing treatment for nAMD reported a 2-line improvement in vision which was, in turn, associated with substantial positive increases in Reading Scores. Improvements in Mobility and Emotional Scores appear to be driven by factors other than visual acuity.